Manajemen program ektrakurikuler pramuka dalam meningkatkan prestasi non akdemik siswa di SMA Negeri Megang Sakti - Firly; Danim, Sudarwan (Manajer Pendididikan, 2025)
This study aims to evaluate the management of the Scout extracurricular program in improving students' non-academic achievements at SMA Negeri Megang Sakti. The research method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the management of the Scout extracurricular program includes systematic planning, effective organization, and continuous evaluation, which impacts students' discipline, leadership, and teamwork. This study provides insights for schools in optimizing extracurricular programs to support students' non-academic achievements.